Maternal, newborn and breast milk concentrations of elexacaftor/tezacaftor/ivacaftor in a F508del heterozygous woman with cystic fibrosis following successful pregnancy - Ripani, Pietro; Mucci, Matteo; Pantano, Stefano; Di Sabatino, Maria; Collini, Francesca; Ferri, Giulia; Romano, Mario; Recchiuti, Antonio (Frontiers in Medicine, 2023)
With the introduction of elexacaftor/tezacaftor/ivacaftor (ETI), more women with cystic fibrosis (CF) are likely to grow families. Hence, an understanding long-term safety and effects of CFTR modulators on fertile women and children while monitoring their concentrations is crucial. Here, we report on the development of an improved LC–MS/MS methodology to measure ETI concentrations in maternal and child blood and breastmilk, applied in one case of successful pregnancy of a 30-year-old woman with CF (F508del/R334W). We observed that ETI remains stable in breastmilk, is absorbed by the infant and can be detected in child plasma. Our results confirm accumulating evidence of a successful pregnancy in women treated with CFTR modulators without significant side effects on the child and provide valuable analytical procedures suitable for the post-marketing evaluation of CFTR modulators in pregnant and lactating women, as well as in their infants.